2010
DOI: 10.1097/mbc.0b013e328331fd00
|View full text |Cite
|
Sign up to set email alerts
|

Carbon monoxide releasing molecule-2 increases the velocity of thrombus growth and strength in hemophilia A, hemophilia B and factor VII-deficient plasmas

Abstract: Carbon monoxide derived from carbon monoxide releasing molecules (CORMs) has been demonstrated to enhance normal plasma thrombus speed of growth and strength in vitro. We tested the hypothesis that tricarbonyldichlororuthenium (II) dimer (CORM-2) improves the velocity of formation and strength of hemophiliac plasma thrombi as determined by thrombelastography. Plasma deficient (<1% normal activity) in factor VIII (FVIII; n = 11 individuals), factor IX (FIX; n = 5 individuals) or factor VII (FVII; n = 4 individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…CORM-2 increases the velocity of thrombus growth and strength in hemophilia A, hemophilia B, and factor VII-deficient plasmas [36]. Furthermore, CORM-2 enhances coagulation and markedly attenuates fibrinolysis in human plasma [37].…”
Section: Discussionmentioning
confidence: 98%
“…CORM-2 increases the velocity of thrombus growth and strength in hemophilia A, hemophilia B, and factor VII-deficient plasmas [36]. Furthermore, CORM-2 enhances coagulation and markedly attenuates fibrinolysis in human plasma [37].…”
Section: Discussionmentioning
confidence: 98%
“…were exposed to CORM-2 [51][52][53][54][55][56][57] In order to further characterize the mechanism by which CO enhanced coagulation, experiments involving isolated exposure of prothrombin [58] or fibrinogen [59] to CORM-2 were performed, with the purified protein function assessed in prothrombin or fibrinogen deficient plasmas, respectively. These works lead to the determination that only fibrinogen was affected by CO [58,59], and additional work utilizing mass spectrometry [60] demonstrated that protease digestion of fibrinogen was modified by exposure to CO. More importantly, it was noted that a heme group(s) was present in the fibrinogen digest samples, and following exposure of human plasma to compounds that either produced a carboxyheme or metheme state, plasma strength was increased or decreased respectively, indicative of heme-based modulation of fibrinogen function [60].…”
Section: In Vitro and Preclinical Evidence That Co Is A Procoagulant mentioning
confidence: 99%
“…4), with methods used to generate these images as previously cited [84][85][86]. Considered together, these investigations involved conditions or disease states wherein increased CO would be expected to be present, resulting in thrombus ultrastructure (e.g., finer or matted fibers) consistent with enhanced clot strength demonstrated in vitro [48,[51][52][53][54][55][56][57]67,68,[70][71][72][73][74][75][76] or in vivo [68,69] following CO exposure.…”
Section: Ultrastructural Findings Supporting a Procoagulant Role For Comentioning
confidence: 99%
See 1 more Smart Citation
“…Concordantly, electron microscopy revealed that thin, strong fibrin fibers (which are also more resistant to fibrinolysis) form to a greater extent in plasma thrombi than thick, weaker fibers in the presence of CORM-2 [14]. Studies with hemophiliac plasma [15], plasma obtained from subjects administered warfarin [16], and plasma diluted with crystalloid or colloid [17] demonstrated improved coagulation kinetics and decreased vulnerability to lysis following exposure to CORM-2. In sum, rather than increase thrombin generation, CORM-2 modifies the substrate characteristics of fibrinogen, thus enhancing coagulation and attenuating fibrinolysis.…”
Section: Introductionmentioning
confidence: 87%